1991
DOI: 10.1063/1.106305
|View full text |Cite
|
Sign up to set email alerts
|

Undoped semi-insulating InP by high-pressure annealing

Abstract: Undoped semi-insulating (SI) InP wafers were obtained by high-temperature annealing under high phosphorus over pressure. These wafers show resistivities higher than 107 Ω cm, with mobilities greater than 4000 cm2 V−1 s−1. The SI properties could be held even after cap annealing with SiNx films at 700 °C for 15 min. The activation energy of deep levels causing the semi-insulation was estimated as 0.64 eV. Photoluminescence measurements made on undoped SI InP show hitherto unknown peaks in the long wavelength re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Fe-doped SI InP has however various disadvantages such as the nonuniformity of electrical properties along crystal growth axis due to Fe segregation, 1 out-diffusion of Fe into epitaxial layers, 2 low activation efficiency of ion implantation, 3 formation of bright spots in substrates, and slip-lines in epitaxial layers. 4 Undoped SI InP, which can be realized by high temperature wafer annealing 5,6 is becoming a promising candidate for replacing conventional Fe-doped InP. The reproducible preparation of undoped SI InP was however difficult and the resistivity (ρ) and the mobility (µ) were largely varied (ρ: 2.6 × 10 3 -2.4 × 10 7 Ω cm, µ: 2080-4740 cm 2 /Vs).…”
Section: Introductionmentioning
confidence: 99%
“…Fe-doped SI InP has however various disadvantages such as the nonuniformity of electrical properties along crystal growth axis due to Fe segregation, 1 out-diffusion of Fe into epitaxial layers, 2 low activation efficiency of ion implantation, 3 formation of bright spots in substrates, and slip-lines in epitaxial layers. 4 Undoped SI InP, which can be realized by high temperature wafer annealing 5,6 is becoming a promising candidate for replacing conventional Fe-doped InP. The reproducible preparation of undoped SI InP was however difficult and the resistivity (ρ) and the mobility (µ) were largely varied (ρ: 2.6 × 10 3 -2.4 × 10 7 Ω cm, µ: 2080-4740 cm 2 /Vs).…”
Section: Introductionmentioning
confidence: 99%
“…For the past decades, various authors have reported the preparation of undoped high resistive or SI InP by wafer annealing [8][9][10][11][12][13], but the reproducibilities have not been enough and moreover the mechanisms of semi-insulation have not been clear yet. In order to realize the reproducible preparation of extremely low Fe doped SI InP, it is necessary to determine suitable annealing conditions for it.…”
Section: Introductionmentioning
confidence: 99%
“…with the carrier concentration of (3)(4)(5) Annealed wafers were removed from the ampoule and they were etched by 50 pm thickness.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently found that undoped semi-insulating InP can be realized when undoped conductive InP is annealed under phosphorus vapor pressure (4,5). The reproducibility of this procedure however was not satisfactory, and the practical use was in delay.…”
Section: Introductionmentioning
confidence: 94%